Model Size Effects on Hallucination Detection Accuracy in Specialized Domains with RAG - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: What is the impact of model size (e.g., comparing Phi-3-mini-4GB to Mistral-7B) on hallucination detection accuracy in specialized domains when using the same RAG pipeline and benchmark datasets. 12 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.4/10. This report is
Machine-generated literature synthesis.